Felinotherapy in nursing homes - Motlová, Lenka (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2018)
Felinotherapy, which is the positive and therapeutic effect of cats on human health, is an important part of the complex health and social care in nursing homes. Felinotherapy is one of the options to make seniors active and support them in this in nursing homes. The goal of this study was to describe the methods and forms used for providing felinotherapy in nursing homes and to analyze its positive effects. This systematic study includes the secondary data analysis – monographs, academic articles and publications found in databases (PubMed). Although many authors have studied the effect of animals on human health, no long-term study proving the effect of felinotherapy on the health of seniors in nursing homes was found. We used the secondary analysis and the author’s experience with zoo therapy to identify the positive effects of felinotherapy in nursing homes in the following domains: (1) emotionally positive experiences, positive mood and the decrease of stress; (2) psychosocial support and physical contact with a cat; (3) positive relationship with animals and the ways of handling a cat; (4) training cognitive functions and reminiscence; (5) relaxation and training concentration; (6) social contact and the assistance in adaptation to nursing homes; (7) cats and caring for them as a conversation topic and a common interest; (8) stimulation and training of the senses; (9) movement, exercising the motoric system; (10) supporting autonomy and independence, gaining the feeling of security.
Felinoterapie v domovech pro seniory
Keywords: Felinotherapy; Nursing home; Activities; Residential social service, zoo therapy; Cat assisted activity and therapy; Cat assisted intervention; felinoterapie; domov pro seniory; aktivizační činnosti; pobytová sociální služba, zooterapie; aktivity a terapie za asistence kočky; intervence za asistence kočky